Bioconversion of vegetable waste on the example of EU countries and Ukraine - Korniienko, I.M.; Huliaiev, V.M.; Anatskyi, A.S.; Filimonenko, O.Yu.; Kuznietsova, O.O.; Yastremska, L.S.; Monchenko, O.V.; Baranovskyy, M.M. (Problems of Environmental Biotechnology, 2023)
The study of the effectiveness of EM-technologies for the bioconversion of vegetable waste, namely, beetroot, carrot and potato was carried out.